Efeito anticárie e propriedades de infiltrantes resinosos incorporados com nano-hidroxiapatita de cálcio e de estrôncio - Cavalcante, Salma Ivanna Araújo (2020)
Aiming to improve the performance of resinous infiltrants in the control of initial caries lesions, by introducing remineralizing capacity to the material, the incorporation of hydroxyapatite nanoparticles has been proposed. Among them, strontium hydroxyapatite (NSrHAp) and calcium (NHAp) nanoparticles have stood out due to potential improvements in the mechanical, biological and remineralizing properties of the materials. The objective of this study was to evaluate the effect of the incorporation of NHAp and NSrHAp, synthesized by the hydrothermal method for 2 h and 5 h, on the roughness and degree of conversion of an experimental infiltrant, as well as on the inhibition of caries lesion adjacent to the infiltrated enamel, constituting the experimental groups: NSrHAp2h, NHAp2h, NSrHAp5h and NHAp5h. Enamel treated with base infiltrant (C) and a demineralized group with phosphoric acid were used as controls. The nanoparticles were then incorporated at a concentration of 5% by weight in C. The degree of conversion (GC- in triplicate) and roughness (n = 10) were evaluated, respectively, by Raman spectrophotometry and by mechanical profilometry, for each infiltrant. Sixty blocks of human enamel were artificially demineralized through pH cycling, treated with experimental infiltrants, and having an adjacent area preserved without any treatment. After carrying out the treatments, the blocks were cut in half and half of each block was submitted again to the pH cycling model. Analysis of microhardness in longitudinal section of the enamel was performed after treatments and after pH cycling in the area adjacent to the infiltrated artificial lesion. Microhardness data were compared by two-way ANOVA and Tukey's test (p <0.05), while the degree of conversion and roughness by one-way ANOVA and Tukey's test (p <0.05). The roughness analysis showed that the incorporation of the nanoparticles was not affected by the pH cycling (p> 0.05). The infiltrating CG did not show statistically different values (p = 0.212). After pH cycling, the NSrHAp2h infiltrant increased the enamel hardness in the region adjacent to the infiltrated area, while the other groups showed a reduction in microhardness (p <0.05). The addition of NSrHAp2h in resinous infiltrants decreased the enamel demineralization adjacent to the infiltrated area and can be an adjunct in the control of initial enamel caries lesions, without interfering with the infiltration roughness and degree of conversion.